Coping Through Religiosity, Spirituality and Social Support Among Muslim Chronic Hepatitis Patients - Sohail, Malik Muhammad (Journal of religion and health, 2020)
Academics acknowledge religiosity, spirituality and social support as socio-behavioral factors that influence patients’ ability to deal with chronic illness. This study has attempted to describe empirical reality of how these factors influence patients. The sample of this study was 500 chronically ill hepatitis patients and was selected through the multistage sampling techniques. Through structured interview schedule, data were collected during the period of September 2016 to March 2017 from five most populated cities of Punjab (Pakistan). Data were analyzed through descriptive (frequency and percentage) and inferential statistics (Cronbach’s alpha, Pearson correlation, and structural equation modeling). The study suggests some recommendations and suggestions to policy makers regarding the significance of religiosity, spirituality and social support as coping strategies during chronic illness. The findings illustrate that social support has more association with coping than religiosity and spirituality of the patients.